Young athletes' ECG: Incomplete right bundle branch block vs crista supraventricularis pattern - Diaz-Gonzalez, L.; Bruña, V.; Velásquez-Rodriguez, J.; Valenzuela, P. L.; Valero-Masa, M. J.; González-Saldívar, H.; Martinez-Sellés, M.; Lucia, A.; Boraita, A. (Scandinavian Journal of Medicine & Science in Sports, 2020)
Background: Incomplete right bundle branch block (IRBBB) is prevalent among athletes, but its etiology remains to be clearly elucidated and the commonly advocated mechanism, an intraventricular conduction delay, does not explain all cases. In the general population, an apparently similar phenomenon but with different pathophysiology and potential consequences, "crista supraventricularis pattern" (CSP, defined as QRS = 100 ms, S wave <40 ms in I or V6 together with an RSR´ pattern in lead-V1) has been described. Yet, this manifestation has not been studied in athletes. Given that IRBBB can be associated with some serious conditions (including Brugada syndrome, arrhythmogenic cardiomyopathy, or atrial septal defects) the differentiation between IRBB and CSP could enhance the accuracy of the pre-participation screening (PPS). We thus aimed to determine the prevalence of CSP in young athletes. Methods: Observational study of standard 12-lead resting ECG in a cohort of children (5-16 years) attending a PPS program (August 2018-May 2019). Results: 6,401 children (mean ± SD age 11.2 ± 2.9 years, 99.2% Caucasian, 93.8% male, 97.2% soccer players) were studied. We found CSP in 850 participants (prevalence = 13.3% [95% confidence interval 12.5-14.1]) whereas 553 (8.6%) had IRBBB. The proportion of athletes showing an S1S2S3 pattern was higher in those with CSP compared with the other QRS morphologies (P < .05). Conclusions: CSP might have been overlooked in previous reports of sports PPS for children and misdiagnosed as IRBBB, as the proportion of the former condition was higher. Our findings might add useful information to improve the interpretation of the young athletes` ECG and thus the diagnostic value of PPS.